PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMPN 13 PEKANBARU MELALUI PENDEKATAN KONTEKSTUAL - Daniel Fernando; Susda Heleni; Sehatta Saragih (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research caused by the low ability of mathematical problems solving student in junior high school 13 Pekanbaru. Purpose of this research are 1) to determine the significance of the improvement of mathematical problems solving ability (MPSA) of grade VII SMPN 13 Pekanbaru students through contextual approach (CA) and through conventional learning (CL); and (2) to determine the difference of MPSA increase of grade VII students of SMPN 13 Pekanbaru which is learned through CA and through CL. The research method was experimental study with pretest and posttest control group design. The population of this study was all of the students from grade junior high school 13 Pekanbaru. The subject was divided into two groups, 7th-5 as experiment group and 7th-8 as control group. The research instruments was essay questions MPSA. Data are analyzed by using Kolmogorov-Smirnov test, Levene test, t-test, and Mann Whitney U tes. The result showned that (1) there was significance of improvement of MPSA of students through CA, (2) there was significance of improvement of MPSA of students who learned through CL, and (3) improvement of MPSA of students who are taught through CA is higher than students who are learned through CL. The improvement of students' mathematical problem solving skills through CA is categorized high while CL is categorized medium.Key Words : Improvement of Mathematical Problems Solving Ability, Contextual Approach